Analysis of time-dependent alterations of parameters related to erythrocytes after ipragliflozin initiation - Yamada, Tomoko (Diabetol Int, 2020)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors often increase the hematocrit. It remains unclear whether this increase would be observed in all patients administered SGLT2 inhibitors, however. We therefore used the data from the previous study and investigated time-dependent alterations of various outcomes related to erythrocytes, erythropoiesis, and clinical outcome in type 2 diabetes subjects (n = 89) treated with ipragliflozin for 16 weeks. Among a total of 89 participants, 71 subjects (80.0% of total participants) showed the elevation of the hematocrit and 18 subjects (20.0% of total participants) did not at 16 weeks. Although the hematocrit levels at baseline were significantly lower in hematocrit-elevated group than non-elevated group, they reached the same levels 4 weeks after the onset of treatment. Binomial logistic regression analysis demonstrated that a lower baseline hematocrit level was related to the elevation of hematocrit at 16 weeks. Optimal cutoff hematocrit levels at baseline to predict hematocrit elevation were 46.9% (male) and 41.7% (female) in ROC analysis. Random intercept model analysis revealed the serum erythropoietin level increased in both hematocrit-elevated and non-elevated groups, whereas only the former group showed an increase in the percentage of reticulocytes during the first 4 weeks. These results suggest that the ipragliflozin-induced increase in hematocrit which is affected by the baseline hematocrit level is attributable to the responsiveness to, but not to the production of, erythropoietin. Collectively, Ht elevation observed in administration of SGLT2 inhibitors can result from erythropoietin-induced erythropoiesis, which is determined by the pre-treatment Ht level. Trial registration: This trial has been registered with University Hospital Medical Information Network Clinical Trial Registry (UMIN-CTR no. 000015478).